Good Governance in Jatimulya Village, Kosambi Sub-District Tangerang District - Muhammad Renaldi; Ahmad Murodi; Fitria Firdiyani (International Journal of Education, Information Technology, and Others, 2023)
This research discusses good governance in Jatimulya Village, Kosambi District, Tangerang Regency. However, from observations and community assessments related to the performance of the village government, there are still weaknesses in realizing the principles of good governance. The problems in this research are: how is good governance in the administration of government in Jatimulya Village, Kosambi District, Tangerang Regency and what are the supporting and inhibiting factors in good governance in the administration of government in Jatimulya Village, Kosambi District, Tangerang Regency. As an effort to increase the role of the village government in realizing good governance, the theory used is based on the concept of Good Governance theory from the United National Depelopment Progam (UNDP) cited by (Sedarmayanti, 2012: 3) which states that to realize good governance, it is necessary to apply the principles of governance by referring to 9 (nine) principles, namely: Participation, Rule of law, Transparency, Responsiveness, Consensus orientation, Equality, Effectiveness and efficiency, Accountability, Strategic vision. The research methods used in this research are observation, interviews, documentation, data management techniques and data analysis, namely data collection, data reduction, data display, and drawing conclusions which are carried out qualitatively. Based on the results of the study, it can be concluded that good governance in the implementation of village governance in Jatimulya Village in realizing the principles of good governance has been implemented, but there are several obstacles in its implementation, namely the low level of human resources (HR), decreased community participation and community disunity towards the village government. The village government's efforts in dealing with obstacles to realizing the principles of good governance are to increase cooperation with institutions to hold seminars to socialize and improve communication to the community.